Prevalence of double burden on malnutrition at household level in four Latin America countries - Hanrieti Rotelli Temponi; Gustavo Velasquez-Melendez (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objectives: to estimate the prevalence of maternal overweight and short stature in children at household level in Brazil, Bolivia, Colombia and Peru. Methods: a cross-sectional descriptive study. Population-based studies on children (0-5 years old) and women (15 to 49 years old) who participated in the Pesquisa Nacional de Demografia e Saúde da Criança e da Mulher(National Survey on Children and Women Demography and Health) in Brazil and the Encuesta Nacional de Demografía y Salud, (National Survey on Demography and Health), in Bolivia, Colombia and Peru. Variables of interest: overweight mother and child with short stature, a double burden when both outcomes are present. Global prevalence and stratification, according to rural and urban areas and 95% confidence intervals, were estimated. Results: the global sample consisted of 26,506 households. The prevalence of double burden was 9.3% in Bolivia (CI95%= 8.3-10.4), 6.7% in Peru (CI95%=5.9-7.5), Colombia (3.2%; CI95%=2.8-3.6) and Brazil (2.2%; CI95%=1.4-3.2). The highest prevalence were observed in the rural areas in Bolivia (13% vs 6.5%; p<0.001) and Peru (11.9% vs 4.1%; p<0.001). Conclusions: the highest prevalence were registered in Peru and Bolivia, and the lowest in Brazil and Colombia.